Analysis of Factors Affecting Pregnant Mothers in Performing VCT Examinations at the Arjasa Public Health Center, Sumenep Regency - Nurwijayanti; Galih Tri Marda Ningrum (Journal for Quality in Public Health, 2022)
HIV/AIDS is a frightening phenomenon for the Indonesian people today, so that people with HIV/AIDS often get very bad stigma and discrimination.The purpose of this study was to analyze the effect of attitudes, family support and service quality on the implementation of VCT examinations for pregnant women at the Arjasa Public Health Center, Sumenep Regency. The design of this research is an observational quantitative study with a cross sectional approach with the focus of the research directed at analyzing the influence of attitudes, family support and service quality on the implementation of VCT examinations for pregnant women at the Arjasa Public Health Center, Sumenep Regency. The total population is 159 respondents and a sample of 108 respondents is taken by the Accidental Sampling technique. In the study it was found that halmost half of the respondents have attitude enough category as many as 47 respondents (43.52%). Most respondents have adequate family support category as many as 49 respondents (45.37%). Most of the respondents have sufficient service quality category as many as 50 respondents (46.30%). Most of the respondents carried out the VCT test as many as 71 respondents (65.74%). Based on the results of the Logistics Regression analysis showed that the p-value <0.05 then H1 was accepted so it was concluded that there was an influence of attitude, family support and service quality on the implementation of VCT examinations for pregnant women at the Arjasa Health Center, Sumenep Regency. It is expected for pregnant women to routinely check the womb in order to maintain the health of the mother and fetus so that the baby is born healthy and the mother is safe.